151k views
2 votes
1/2z+6=3/2(z+6) need the answer asap

2 Answers

3 votes

Answer:

z=−3

Explanation:

1/2*z+6-(3/2*(z+6))=0

Simplify 3/2

1 3

((— • z) + 6) - (— • (z + 6)) = 0

2 2

Simplify 1/2

Rewrite the whole as 6.1 Pull out like factors :

-2z - 6 = -2 • (z + 3) a fraction using 2 as the denominator.

-z - 3 = 0

7.1 Solve : -z-3 = 0

Add 3 to both sides of the equation :

-z = 3

Multiply both sides of the equation by (-1) : z = -3

User Ilya Semenov
by
6.4k points
6 votes

Answer:

z = -3

Explanation:


(1)/(2)z+6 =
(3)/(2)(z+6)

Expand and cancel out brackets.


(1)/(2)z+6 =
(3)/(2)z +

Simplify.


(1)/(2)z+6 =
(3)/(2)z + 9

Isolate x and numbers.


(3)/(2)z -
(1)/(2)z = 6-9

Simplify.


(2)/(2)z = -3

z = -3

User Bao HQ
by
5.1k points